AN EMPIRICAL INVESTIGATION OF FACTORS AFFECTING ENTREPRENEURIAL CAPABILITY (EC) ENVIRONMENT IN ASEAN-5 ECONOMIES - Munshi Naser Ibne Afzal; Shamim Ahmad Siddiqui; Kasim bin Hj. Md. Mansur; Rini Suryati Sulong (Asian Academy of Management Journal, 2018)
The entrepreneurial capability (EC) environment of a given local or regional system refers to a set of social and economic factors that exert influence on entrepreneurial processes occurring within said system. To this end, the goal of the currently presented work is to determine and empirically validate the said EC factors in relation to the entrepreneurial environments of the Association of South East Asian Nations (ASEAN)-5, namely Indonesia, Thailand, Singapore, Malaysia, and the Philippines, both at the regional and national levels. For this purpose, the presented research adapted the entrepreneurial perceived capabilities framework to first investigate the key determinants of EC that affect key entrepreneurial processes, such as the seeking of new opportunities and the decision to venture into new commercial opportunities, within the context of ASEAN-5 economies. Next, the identified variables were empirically tested via an examination of their coefficients in relation to their impact on entrepreneurial perceived capabilities. Succinctly, the current work applied recent consistent estimation of panel bootstrap random-effects model to determine time variant changes with respect to the studied variables in the panel sample. The data used in the current work was obtained from the Global Entrepreneurship Monitor (GEM) and World Competitiveness Yearbook (WCY) databases for the years 2010–2016. The results of the current work suggest that factors such as beliefs regarding entrepreneurship as a good career choice (EnGC) and perceived opportunities (PO) yield significant positive impact on the efficiency of EC in ASEAN-5, and can be nurtured to further improve EC environments both at the regional and national levels. Conversely, the fear of failure (FefRa) variable was shown to exert considerable negative impact on the efficiency of ASEAN-5 EC environments. Variables such as intellectual property rights (IPR), university education (UE), and knowledge transfer rate (KT) were also shown to have a positive impact on both national and regional ASEAN-5 EC environments. The current work thus makes a valuable contribution to the associated literature by presenting a robust empirical analysis of EC factors of ASEAN-5 economies, the results of which can be used to inform policies aimed at strengthening the EC settings of ASEAN-5 with respect to their pursuit of an innovation-driven region.